The Effect of Environmental Enrichment on Glutathione-Mediated Xenobiotic Metabolism and Antioxidation in Normal Adult Mice - Seo, Jung Hwa; Pyo, Soonil; Shin, Yoon-Kyum; Nam, Bae-Geun; Kang, Jeong Won; Kim, Kwang Pyo; Lee, Hoo Young; Cho, Sung-Rae (Frontiers in Neurology, 2018)
Olfactory bulb (OB) plays an important role in protecting against harmful substances via the secretion of antioxidant and detoxifying enzymes. Environmental enrichment (EE) is a common rehabilitation method for rodents and known to have beneficial effects in the central nervous system. However, the effects of EE in the intact OB still remain unclear. At 6 weeks of age, CD-1® (ICR) mice were assigned to standard cages or EE cages. After two months, we performed proteomic analysis. 44 up-regulated proteins were identified in EE mice compared to the control mice. Further Gene Ontology analysis and Kyoto Encyclopedia of Genes and Genomes Pathway enrichment demonstrated that the up-regulated proteins were mainly involved in metabolic pathways against xenobiotics. Among those up-regulated proteins, 9 proteins, which participate in phase I or II of the xenobiotic metabolizing process, were validated by qRT-PCR. These upregulated proteins, especially phase II enzymes, are known to be responsible for ROS detoxification. To explore the effect of ROS detoxification mediated by EE, glutathione activity was measured by an ELISA assay. The ratio of reduced glutathione (GSH) to oxidized glutathione (GSSG) was significantly increased in EE mice. Based on a linear regression analysis between the upregulated xenobiotic metabolizing proteins and GSH/GSSG ratio, GSTM2 and UGT2A1 were found to be the most influential genes in ROS detoxification. For further analysis of neuroprotection, inducible nitric oxide synthase (iNOS) level was confirmed using qRT-PCR, and apoptotic process was measured using western blot. The level of iNOS and the ratio of Bax to Bcl-2 were significantly decreased in EE mice. For assessing neuroprotection and cell proliferation, a TUNEL assay and histological assessment with Ki67 were conducted. While TUNEL+ cells were significantly decreased, and Ki67+ cells were significantly increased in the mice reared in EE, implicating that EE creates an optimal state for xenobiotic metabolism and antioxidant activity. Taken together, our results suggested that EE protects olfactory layers via the up-regulation of glutathione-related antioxidant and xenobiotic metabolizing enzymes, eventually lowering ROS-mediated inflammation and apoptosis and increasing neurogenesis. This study may provide an opportunity for a better understanding of the beneficial effects of EE in the OB.